A Randomized Controlled Trial: Colistin Alone or Colistin and Meropenem: Which Is More Effective for the Management of Urinary Tract Infections? Colistin with and without Meropenem for Management of Urinary Tract Infections - Yadegarynia, Davood; Tehrani, Shabnam; Keyvanfar, Amirreza; Gachkar, Latif; Najafi, Behnaz (Novelty in Biomedicine, 2022)
Background: Colistin is a common antibiotic used to treat urinary tract infections (UTIs) caused by gramnegative bacteria. In recent years, due to the increasing resistance, consumption of colistin alone could lead to treatment failures. This study aimed to compare the effectiveness of colistin alone with colistin and meropenem to treat patients with urinary tract infections. Materials and Methods: In this randomized, open-label, parallel groups controlled trial, hospitalized patients with urinary tract infections were included. Patients were randomly allocated to the control group (n=35) that received colistin (1 mIU every 12 hours) and the intervention group (n=35) that received colistin (1 mIU every 12 hours) with meropenem (1gr every 8 hours). An infectious disease specialist evaluated the therapeutic responses 48-72 hours after admission. Cessation of fever, improvement of symptoms and signs, and negative urine culture within 48 hours were considered successful therapeutic responses. Results: The mean length of hospitalization was longer in the control group (4.74±0.78 days) compared with the intervention group (4.26±0.56 days) (P=0.004). The prevalence of fever cessation had no significant difference between the two groups at any time (P>0.05). Also, there was no significant difference between the two groups at any time, considering vital signs, irritative urinary symptoms, nausea and vomiting, and flank pain (P>0.05). Conclusion: The administration of colistin and meropenem to treat UTIs was associated with a shorter length of hospital stay. However, regarding response to treatment, it did not matter if they were treated with colistin alone or with combination therapy (colistin and meropenem)